Relationship between Consumer Characteristics and Impulse Buying Behavior: The Mediating Role of Buying Intention of New Clothing Buyers - Abbasi, Badri (International Review of Management and Marketing, 2017)
The purpose of this study was to determine the relationship between consumer characteristics and impulse buying behavior focusing on buying intention. This survey used a descriptive applied methodology and causal correlation. Participants included new clothing buyers in malls of Rasht during autumn and winter. Data was collected by questionnaire. Results of factor analysis indicated high reliability of the constructs. Results showed that self-esteem, followed by new product knowledge and excitement, respectively, had the greatest effect on impulse buying behavior. The results provided a basis for implementing strategies to take advantage of consumer characteristics for more sales and optimal productivity. Keywords: Impulse buying behavior, buying intention, product knowledge, self-esteem, excitement JEL Classifications: M3, M31